Biosorption Removal of Methylene Blue Dye From Aqueous Solution Using Modified Sugarcane Bagasse - Clara, Wong Xiang Xiang (Penerbit Universiti Malaysia Perlis, 2010)
This research was on the activated carbon produced from sugarcane bagasse, existing wide as waste in Malaysia and other countries producing sugar, for dye removal. Two different activated carbons (AC1 and AC2) were synthesized and their physical characteristics were evaluated against the activated carbons produced using sugarcane bagasse by other researchers, and also against commercial activated carbons. Results showed that AC2 has potential as effective adsorbent than AC1. BET analysis shown that AC2 has high surface area, 503.5470 m2 g-1, and were generally mesoporous. The adsorption of Methylene Blue (MB) dye was examined through batch adsorption experiments as a function of initial dye concentration, contact time, adsorbent dosage and pH. Under optimum pH (pH 10), minimal dosage of adsorbent (0.7 g) was required for complete removal of 100 mL of MB (100 mg/L) in comparison with the dosage required under non-optimum pH. The adsorption data obtained were analyzed using Langmuir and Freundlich isotherms. Langmuir model appeared to fit the isotherm data better than the Freundlich model with qm = 32.8 mg/g (AC1) and 46.3 mg/g (AC2), KL = 0.038 L/mg (AC1) and 0.099 L/mg (AC2), KF = 3.45 (AC1) and 11.63 (AC2), and 1/n = 0.4439 (AC1) and 0.2749 (AC2).